CITYSCAPES OF THE DELHI SULTANATE: A STUDY OF URBANIZATION AND ITS IMPACT - Nisha, Pallavi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Delhi Sultanate marked a transformative period in India’s urban history, characterized by the expansion of cities, the establishment of new urban centers, and the revival of older settlements. With the rise of successive dynasties Mamluks, Khaljis, Tughlaqs, Sayyids, and Lodis—the subcontinent witnessed rapid urbanization driven by administrative needs, military strategies, economic growth, and cultural exchange. The influx of Persian, Central Asian, and Arab influences played a significant role in shaping the architecture, trade networks, and social fabric of these cities. Delhi, the capital of the Sultanate, emerged as a vibrant metropolis, reflecting the grandeur of Islamic urban planning and governance. Other cities such as Lahore, Jaunpur, Daulatabad, and Lakhnauti flourished as regional power centers. These cities were strategically developed with fortifications, mosques, madrasas, caravanserais, and bustling markets that facilitated trade and commerce. Economic activities played a crucial role in urban expansion, with the introduction of a monetized economy, market regulations, and improved trade routes connecting India with the Middle East, Central Asia, and Southeast Asia. The Sultanate encouraged the growth of specialized artisan communities, guilds, and commercial establishments, fostering a vibrant economic environment. The urbanization under the Delhi Sultanate also had a profound socio-political impact. The cities became centers of political authority, military organization, and religious patronage. The architectural legacy of the period, including iconic structures like the Qutub Minar, Alai Darwaza, Hauz Khas Complex, and Tughlaqabad Fort, continues to define India's historical landscape. Despite the prosperity of these urban centers, challenges such as frequent Mongol invasions, shifting capitals, and agrarian dependencies influenced the stability of urban life. Nevertheless, the urbanization initiated during the Sultanate period laid the foundation for the flourishing cities of the Mughal era and beyond, leaving a lasting imprint on India’s historical and cultural development.